2018
DOI: 10.3389/fchem.2018.00096
|View full text |Cite
|
Sign up to set email alerts
|

ParaCEST Agents Encapsulated in Reverse Nano-Assembled Capsules (RACs): How Slow Molecular Tumbling Can Quench CEST Contrast

Abstract: Although paraCEST is a method with immense scope for generating image contrast in MRI, it suffers from the serious drawback of high detection limits. For a typical discrete paraCEST agent the detection limit is roughly an order of magnitude higher than that of a clinically used relaxation agent. One solution to this problem may be the incorporation of a large payload of paraCEST agents into a single macromolecular agent. Here we report a new synthetic method for accomplishing this goal: incorporating a large p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…The model discussed in this sub-section has been confirmed in Payne et al [41], Yadav et al [124], Farashishiko et al [125], and Sharma and Chandra [126].…”
Section: Water Behavior In the Presence Of Inorganic Ions: The Dynamisupporting
confidence: 67%
See 1 more Smart Citation
“…The model discussed in this sub-section has been confirmed in Payne et al [41], Yadav et al [124], Farashishiko et al [125], and Sharma and Chandra [126].…”
Section: Water Behavior In the Presence Of Inorganic Ions: The Dynamisupporting
confidence: 67%
“…More in detail, they behaved as chaotropes up to the concentration of 4 M. Conversely, they showed a kosmotropic behavior above the aforementioned concentration. From a qualitative standpoint, the different effects could be explained considering the prevalence of the chaotropic nature of the cations (either Na + or NH 4 + ) when concentrations were < 4 M and by the prevalence of the kosmotropic nature of nitrate when salt concentration was > 4 M. The model discussed in this sub-section has been confirmed in Payne et al [41], Yadav et al [124], Farashishiko et al [125], and Sharma and Chandra [126].…”
Section: A Ffc Nmr-based Model For Nutrient Dynamics In Soilsmentioning
confidence: 58%
“…38,39 In addition, CEST agents based on polymers or liposomes have been designed as vascular agents, exhibiting good CEST contrast, despite some not having been tested in vivo yet. [40][41][42][43][44][45][46] Also, molecules that possess exchangeable hydroxyl groups (-OH) as dextrans can be detected by MRI-CEST without extra labeling procedures. [47][48][49][50][51][52][53] Recently, it was found that dextran molecules with different molecular weights are able to provide a size-dependent CEST contrast.…”
Section: Introductionmentioning
confidence: 99%
“…Low‐molecular‐weight iodinated agents, clinically approved for X‐ray investigations, have been exploited as perfusion agents for MRI‐CEST application 38,39 . In addition, CEST agents based on polymers or liposomes have been designed as vascular agents, exhibiting good CEST contrast, despite some not having been tested in vivo yet 40‐46 . Also, molecules that possess exchangeable hydroxyl groups (‐OH) as dextrans can be detected by MRI‐CEST without extra labeling procedures 47‐53 .…”
Section: Introductionmentioning
confidence: 99%
“…The saturated exchangeable protons then exchange with bulk water protons, resulting in partial loss of the bulk water signal, which then becomes detectable during MRI [32]. CEST MRI can be switched “on” and “off” at will by simply adjusting the RF saturation pulse sequence parameters [33]. Notably, CEST MRI has potential to provide molecular information for diagnosing pathological tissues and detecting molecular responses to treatment [34, 35].…”
Section: Introductionmentioning
confidence: 99%